PEMODELAN UJUNG BATANG DAN KAIT GORDEN DENGAN KURVA BÉZIER - Istiqomah, Rokhmatul; Juliyanto, Bagus; Ubaidillah, Firdaus (Jurusan Matematika FMIPA Universitas Jember, 2021)
The end cup consists of the crown, head and neck, while the hook consists of a stand and a hook. This study aimed to obtain various of shapes vary. The modeling can be done with deformation techniques such as interpolation and Bezier curves. The method of this study uses three step namely constructing the basic objects of the geometry, arranging these basic objects on one modeling axis, and visualization with Maple 18. This study obtained 160 the models of end cup and 8 models hook consisting of geometric shapes of tube, cone, sphere, the beam, torus, and the octagonal prism.